Maternal provisioning by foam-nesting frogs of the genus Physalaemus (Anura, Leptodactylidae) in contrasting environments - Pupin, Nadya C. [UNESP]; Haddad, Célio F.B. [UNESP]; Prado, Cynthia P.A. [UNESP] (De Gruyter, 2018)
In some environments prevailing conditions are unpredictable, thus anuran species use bet-hedging strategies and produce eggs of varied sizes. We investigated whether four species of Physalaemus (two from open, two from forest habitats) exhibit bet-hedging strategies, and if intra-clutch variation in egg size is greater for species that breed in the more unpredictable ponds of open habitats. All species studied adopted the bet-hedging strategy, with intra-clutch variation in egg size regardless of the environment; however, we found greater intra-clutch variation in the two species from open areas. The lower variation in egg-size found within forest habitats may be explained by the more stable environments that forest ponds provide for anuran eggs/embryos. Future studies in a phylogenetic context are needed to confirm the patterns detected here.
Keywords: bet-hedging; egg size; forest; intra-clutch variation; open area; temporary pond